How working from home influences perceived flow in achieving integral human development - Aguilar, Rachel C. (Animo Repository, 2022)
PurposeWith the COVID-19 pandemic changing the course of most businesses, the authors explored the effects of a digital setup regarding the perceived personal and team flow and integral human development. The scope is limited to student-owned online businesses within Metro Manila. Methodology, Design, and ApproachThe authors adopted a qualitative research method to garner deeper insights from the respondents. The research design was composed of a semi-structured online interview and a pseudo-virtual ethnographic approach to understand the respondents’ perspectives. FindingsThe businesses experienced desirable and undesirable effects of shifting to the work-from-home setup. Moreover, the nature of the business and the existing relationships prior to creating the team also played a role in affecting their personal and team flow, which developed and hindered certain aspects of their integral human development. Research limitations/implicationsConsidering the pandemic, data collection methods were restricted to online approaches. The target respondents were undergraduate university students aged 18-24 years old. The scope included both (a) current students and (b) graduates who started the business when they were still students. Practical and social implicationsInsights gained from the study may assist student-owned enterprises struggling amidst the pandemic and encourage productive and thriving well-being. Originality and ValueThis paper examined the advantages and disadvantages of work-from-home setups for different businesses, how they transitioned and continued operations, and how these changes have affected the respondents' individual and team dynamics and their overall integral human development. This paper will be unique in its setup, timing, and conclusion.